2020
DOI: 10.1186/s13065-020-00675-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of 2-(4-methylsulfonyl phenyl) indole derivatives: multi-target compounds with dual antimicrobial and anti-inflammatory activities

Abstract: Three series of 2-(4-methylsulfonylphenyl) indole derivatives have been designed and synthesized. The synthesized compounds were assessed for their antimicrobial, COX inhibitory and anti-inflammatory activities. Compound 7g was identified to be the most potent antibacterial candidate against strains of MRSA, E. coli, K. pneumoniae, P. aeruginosa, and A. baumannii, respectively, with safe therapeutic dose. Compounds 7a-k, 8a-c, and 9a-c showed good antiinflammatory activity with excessive selectivity towards CO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Reviewing the synthesis methods of 2-phenylindole compounds over the past two decades is indeed valuable for researchers looking to develop new indole-based drugs. The wide utilization of the 2-phenylindole skeleton in studying anticancer, bacteriostatic, and anti-inflammatory activities underscores its importance in drug discovery and development. ,, By examination of various synthesis approaches outlined in the literature, researchers can gain insights into efficient and sustainable methods for producing these pharmacologically significant compounds, facilitating the exploration of novel indole-based therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing the synthesis methods of 2-phenylindole compounds over the past two decades is indeed valuable for researchers looking to develop new indole-based drugs. The wide utilization of the 2-phenylindole skeleton in studying anticancer, bacteriostatic, and anti-inflammatory activities underscores its importance in drug discovery and development. ,, By examination of various synthesis approaches outlined in the literature, researchers can gain insights into efficient and sustainable methods for producing these pharmacologically significant compounds, facilitating the exploration of novel indole-based therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, triazoles and sulfonamides are important fragments present in the structure of marketed small molecule drugs with a wide range of bioactivities such as antibacterial, analgesic, anti-inflammatory, anti-tumor, and antiviral activities, and thus possess excellent pharmacological applications. (Haider et al, 2013;Abdellatif et al, 2016;Bonandi et al, 2017;Akgul et al, 2018;Pandit et al, 2018;Bozorov et al, 2019;Zhang, 2019;Shaker et al, 2020;Zhang et al, 2021b;Dai et al, 2022;Du et al, 2023). Therefore, we hypothesized that the introduction of azido and sulfonyl groups to the simplified structure of akuammiline alkaloid picrinine might result in improved and complementary anti-RA effects.…”
Section: Introductionmentioning
confidence: 95%
“…The results of anti‐inflammatory activity confirmed that compound (5‐fluoro‐1 H ‐indol‐2‐yl)(4‐(4‐hydroxyphenyl)piperazin‐1‐yl)methanone exhibited excellent inhibitory effect against the COX‐2 enzyme. Shaker and co‐workers [102] continue their investigations on a series of novel indole ( 61 ) derivatives as anti‐inflammatory agents. The synthesized derivatives were evaluated for their anti‐inflammatory and COX inhibitory activities.…”
Section: Bioactivity Evaluationmentioning
confidence: 99%